Fabry disease screening in high-risk populations in Japan: a nationwide study - Yoshida, Shinichiro (Orphanet J Rare Dis, 2020)
BACKGROUND: Fabry disease (FD) is a X-linked inherited disorder caused by mutations in the GLA gene, which results in the deficiency of α-galactosidase A (α-Gal A). This leads to the progressive accumulation of metabolites, which can cause multisystemic dysfunction. A recent screening study among neonates reported an increase in the incidence of FD, and numerous FD patients remain undiagnosed or even misdiagnosed. Therefore, this study aimed to identify patients with FD by performing high-risk screening in 18,135 individuals, enrolled from October 2006 to March 2019, with renal, cardiac, or neurological manifestations from all prefectures in Japan. A total of 601 hospitals participated in this study. RESULTS: Low α-Gal A activity was detected in 846 individuals, with 224 of them diagnosed with FD by GLA sequencing. Cases with a family history of FD (n = 64) were also subjected to sequencing, without α-Gal A assay, as per individual request, and 12 of them were diagnosed with a variant of FD. A total of 236 patients with FD (97 males and 139 females) were identified from among 18,199 participants. A total of 101 GLA variants, including 26 novel variants, were detected in the 236 patients with FD from 143 families, with 39 amenable variants (39%) and 79 of the 236 patients (33%) suitable for migalastat treatment. CONCLUSIONS: From among 18,199 participants, 101 GLA variants, including 26 novel variants, were identified in the 236 patients with FD from 143 families. Migalastat was identified as a suitable treatment option in 33% of the patients with FD and 39% of the GLA variants were detected as amenable. Therefore, the simple screening protocol using dried blood spots that was performed in this study could be useful for early diagnosis and selection of appropriate treatments for FD in high-risk and underdiagnosed patients with various renal, cardiac, or neurological manifestations.